Reasoning for results - Bray, Dennis (Himalayan Journal of Sciences, 2006)
If biology were just a matter of gathering data about a fixed reality, there would probably be no need for theory in biology. But, basically it is a new idea that makes some significance to the society. Now, more than ever, we need to acknowledge the need for what Bush Père referred to as “the vision thing.” We’re not just talking about discoveries, new techniques, and Big Ideas – all of which require thought, and often hypothesis. Now we are entering a new phase in biology, where computer modeling can create virtual realities – and even predict and shape real reality. It’s a brave new world, and without theorists to reflect on where it’s all going, it could get scary. (Summary is not from Nature; added with the permission by Himalayan Journal of Sciences).This article is reprinted with permission from Nature, Volume 412, Issue 6850, page 863. Copyright © 2001 by Macmillan Magazines Ltd, England.Full text available in the print version of the journalHimalayan Journal of Sciences 1(2): 79-80, 2003